The problem of Deviantism and its Essence - Rahil Najaf (Zien Journals, 2021)
The article emphasizes that deviant behavior is a set of social forms of behavior in the life of individuals who make up society, which are characterized by their own characteristics and are not alien to the social sphere. It is argued that the nature, essence and, most importantly, the cause of behavior is the subject of interesting social and psychological research. It is noted that the main source of deviantism is the search for a social system with a wide social spectrum. In terms of updating social systems, their influence on the psyche and awareness of people is increasing. It is very difficult to find an initial deviation in a person. At first glance, this is almost not observed. However, preventing complications and inflammation is very difficult. The difficulty is connected with the fact that the person does not feel guilty and considers it normal, but in fact the situation is very difficult and frightening. pull you down the road.
Keywords: Deviant behavior; social and psychological factor; civilization; social and moral qualities